Comprehensive analysis of influencing factors and mechanism of nano emulsion spontaneous imbibition oil displacement in tight sandstone reservoir - Li, Zhuang (Frontiers in Energy Research, 2023)
Tight sandstone reservoir has the characteristics of low porosity, low permeability and strong reservoir heterogeneity, which leads to a rapid decline in single well production after hydraulic fracturing. Adding nano emulsion to fracturing fluid can not only realize the dual function of fracturing and imbibition oil displacement, but also effectively prolong the stable production time of oil wells. In order to improve the understanding of the interaction between nano emulsion and reservoir, this paper based on the basic physical property test and analysis of nano emulsion, macroscopic and microscopic spontaneous imbibition oil displacement experiments, the mechanism of imbibition displacement of nano emulsion in tight sandstone reservoirs and the influence of related factors is clarified. The results show that: ①The particle size of the three types of nano emulsions ranges from 11 to 16 nm, and they can enter the nanopore throats deep in the reservoir, and can achieve good injectivity in tight reservoirs. The anionic AES nano emulsion is superior to cationic ADT and nonionic AEO-9 nano emulsion in terms of injectability, oil-water interfacial tension and wetting modification effect in tight sandstone cores, and the optimal concentration is 0.30 wt%. ②Spontaneous imbibition oil displacement experiments show that the nano emulsion concentration is not the higher the better. Since the nano emulsion adsorption on the solid surface reaches a dynamic equilibrium, the excessive nano emulsion cannot further change the wettability of the solid surface, and the lower oil-water interfacial tension has the opposite effect on the imbibition displacement. ③The migration and gathering of emulsified oil droplets in solution mainly included five processes: Saturated oil core/Nano-surfactant fluid emulsion reaction, Aqueous/Emulsified oil droplets, Emulsified oil droplet gathering phase, Demulsifying and emulsifying oil droplets, Oil phase after demulsification. The generation of remaining oil in porous media is due to the non-uniform wetting modification in different regions. This study further improves the understanding of the mechanism of spontaneous imbibition of nano emulsion in tight sandstone reservoirs.